As narrativas intermidiáticas e enviesadas do Romance Gráfico Aqui de Richard McGuire - Machado, Luiz Carlos (2022)
The research presented here focused on the study of intermediality, a concept that designates the interweaving of media and overcoming media boundaries, aiming to analyze the biased narratives of Richard McGuire's Graphic Novel Here (2014). From this proposed analysis, the following question arises: Can the Graphic Novel, taken by the bias of a skewed narrative, be proposed as an intermediate materiality that breaks the boundaries of literary and visual media and expands reading possibilities? With the purpose of finding an answer to this questioning, the general objective is to examine the intermediate narratives of the graphic novel, in order to understand its aesthetic resources that aim to transpose the limits of languages, supports and reading hierarchy. In the perspective of reaching the proposed objective, the research is supported by the theoretical assumptions of intermediality by Rajewsky (2012), Clüver (2011), Moser (2006), the concept of biased narratives by Canton (2009) and the studies on History in comics and Graphic Novel by Eisner (1999) and McCloud (2005). It is, therefore, a research based on comparative literature, of a qualitative nature. As a result of this research process, it was understood that the Graphic Novel seems to be a materiality that proposes an intermediate and biased narrative that offers a possibility of wide, open and conceptual reading.